Analisis Sanitasi Dasar Wilayah Pesisir Desa Kairatu Dusun Pakarena - Sunik Cahyawati (JURNAL RISET RUMPUN ILMU KESEHATAN, 2022)
Basic sanitation is a community effort that focuses on controlling the physical structure, where people use it as a shelter that affects the degree of human health. The purpose of this study was to determine the description of basic sanitation facilities in Kairatu Village, Pakarena Coastal Area in 2021 which includes facilities for providing clean water, toilet and bathroom facilities, waste water management facilities and waste disposal facilities. This type of research is descriptive research, namely the research method carried out with the aim of making a description or descriptive of an objective situation. which was carried out in Kairatu Village, Pakarena Coastal Area in 2021. Provision of clean water facilities in Pakarena hamlet, there are 11 existing families, own property, odorless, colorless, tasteless while there are 4 existing families, but not their own, odorless, colorless and tasteless. On average, Pakarena hamlet residents have a latrine, the type of latrine used is goose neck and has a saptic tank of 14 families and 1 family who does not use a goose neck latrine. Waste water management facilities have not met the requirements. A total of 14 families of waste water are channeled into open sewers and 1 family has SPAL that does not pollute the water. Garbage disposal facilities do not meet the requirements, garbage boxes are not available at all and residents only throw garbage in rivers near settlements while some residents manage waste by burning so that it can pollute the environment.